Management and Prognosis of Primary Cerebral Melanocytic Tumors. A Case Report and Systematic Review - Splavski, Bruno; Muzevic, Dario; Kovacevic, Marko; Splavski, Brano, Jr.; Bajek, Goran (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Primary melanocytic cerebral tumors form a spectrum of different lesions that range from benign to extremely malignant, such as an intracranial melanoma. This article points out some characteristics of primary melanocytic cerebral tumors and discusses their management and prognosis, based on a systematic literature review and a case of primary cerebral malignant melanoma.Because the biological characteristics of primary melanocytic cerebral tumors remain unclear, it appears that total surgical resection of the tumor followed by oncologic treatment is the mainstay of the management. The prognosis still depends on the degree of malignancy.
Keywords: primary melanocytic cerebral tumor; management protocol; prognosis; systematic review